2006
DOI: 10.1097/01.prs.0000239560.29172.33
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelet Plasma Growth Factors in Male Pattern Baldness Surgery

Abstract: This study provides a new perspective and contribution to baldness surgery with follicular unit megasessions, and demonstrates an improvement that can be introduced into baldness surgery clinics with less morbidity and a low cost-to-benefit ratio. Further studies may improve the efficiency of the technique and allow digital programs to better evaluate the increase in hair density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(211 citation statements)
references
References 22 publications
11
188
1
11
Order By: Relevance
“…The significant correlations were seen between these two populations abnormally. These abnormal correlations can leads to abnormalities like AGA [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The significant correlations were seen between these two populations abnormally. These abnormal correlations can leads to abnormalities like AGA [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[8,10] It also appears to increase the perifollicular vascular plexus through the increase of VEGF and PDGF levels, which have angiogenic potential. [11] Uebel et al [5] showed that pretreatment of follicular units with PRP before transplantation resulted in improved hair growth and density. The positive effect of PRP in the treatment of AGA has been documented in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[4] It is hypothesised these growth factors may act on stem cells in the bulge area of the follicles, stimulating the development of new follicles and promoting neo-vascularisation. [5] Skin needling is a technique that uses a sterile dermaroller to puncture the skin and release growth factors. Hence, PRP can be combined with skin needling to enhance the efficacy of both modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Uebel et al [13] observed a significant improvement in hair density and stimulation of growth when follicular units were pre-treated with platelet plasma growth factors before their implantation. There was a significant difference in the yield of follicular units on comparing the experimental with the control areas of the scalp.…”
Section: Vascular Endothelial Growth Factor Regulation Of Angiogenesismentioning
confidence: 99%